THE EFFECTS OF QUALITY, ECONOMIC, SOCIAL, AND CAREER MOTIVATION ON PUBLIC ACCOUNTANTS' INTEREST IN TAKING THE CPA EXAM - Oeyardi, Jesselyn; Yanti, Yanti (International Journal of Application on Economics and Business, 2025)
This study intends to examine how public accountants' interest in pursuing CPA certification is influenced by their motivational factors, including quality motivation, economic motivation, social motivation, and career motivation. There are 71 public accountants who responded to this study by purposeful sampling. The application SmartPLS was used to test the hypothesis. According to the study, quality motivation and career motivation did not have a significant influence on the public accountant's interest in obtaining CPA certification, while economic motivations and social motivation had a significant impact on public accountants' interest in getting CPA.